Evaluasi Manajemen Sumber Daya Manusia Berbasis Human Capital Management: Studi Kasus STAKATN Pontianak - Filianus Nasu Rusik; Usman Radiana; Muhammad Syukri (CV. Multi Kreasi Media, 2023)
In this paper, a description of the implementation of the human resource management program based on Human Capital Management (HCM) at the state-owned theology academy (STAKATN) located in Pontianak, West Kalimantan, Indonesia is presented. The HCM-based human resources management in STAKATN Pontinak was evaluated based on the Context, Input, Process, and Product (CIPP) evaluation model. The data needed for this research was obtained by interviewing head officers, legal documents check and observing the physical aspects and educational activities in STAKATN Pontianak. In conclusion, the implementation of the human resource management program based on HCM at State Catholic University Pontianak (STAKATN), reviewed through the aspect of context, input, process, and product, has not been at the maximum level. The implication is that the governing board of STAKATN Pontianak needs to improve its programs related to the completeness of strategic planning documents, the availability of facilities and budget allocation, and effective communication with the government.